MEKANISME TATA KELOLA KORPORAT: MAMPUKAH MENURUNKAN COST OF EQUITY CAPITAL? - - Tarjo (InFestasi, 2010)
This objective of this study is to analyze the effect of good corporate governance mechanism that consist of board of commissioners’ independence, information transparency, and audit committee on the cost of equity capital. Board  of commissioners independence, information transparency, and audit committee are able to role as the mechanism good corporate governance.The result showed that cost of equity capital is effected by board  of commissioners independence, information transparency, and audit committee. Thereby in order to reduce cost of equity capital those three variable must be well managed by means of good corporate governance effective.